2010
DOI: 10.1017/s1431927610058526
|View full text |Cite
|
Sign up to set email alerts
|

Al2024-CNTs composites by mechanical alloying

Abstract: Carbon nanotubes (CNTs) were dispersed by mechanical milling into a 2024 aluminum alloy (Al 2024 ) in order to produce composites and study the influence of CNTs content over the mechanical and microstructural behavior of them. The time of milling was set to 5 h [1] and the addition of CNTs was of 0.0 to 5.0 wt. %. Powders obtained from milling process were cold compacted and then sintered under argon atmosphere by 2h with 5ºC/min for heating and cooling rates. The microstructural analysis was carried out by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
12
1
1
Order By: Relevance
“…During the EDS analysis all the main alloying elements (i.e., Al, Cu, Mg, and Mn) were considered, however only Cu-containing particles were present ( Fig.4(b)). Similar results were reported by Bustamante et al [16] who studied the microstructure of a 5.0 wt.% CNT/2024Al composite after sintering, and observed a good dispersion of Al 2 Cu coarse particles due to the low cooling rate in the sintering process. The presence of this phase will be further confirmed via XRD phase analysis.…”
Section: Microstructure and Ebsd Analysissupporting
confidence: 89%
See 4 more Smart Citations
“…During the EDS analysis all the main alloying elements (i.e., Al, Cu, Mg, and Mn) were considered, however only Cu-containing particles were present ( Fig.4(b)). Similar results were reported by Bustamante et al [16] who studied the microstructure of a 5.0 wt.% CNT/2024Al composite after sintering, and observed a good dispersion of Al 2 Cu coarse particles due to the low cooling rate in the sintering process. The presence of this phase will be further confirmed via XRD phase analysis.…”
Section: Microstructure and Ebsd Analysissupporting
confidence: 89%
“…The formation of Al 4 C 3 could also be related to the shortening of CNTs as shown in Fig.5(a), leading to an increasing number of carbon atoms at the CNT tips which would enhance the probability of CNT-Al reactions during severe plastic deformation at high temperatures. Bustamante et al [16] showed the XRD results of CNT/2024Al composites as a function of CNT content, and observed that the magnitude of the Al 4 C 3 peaks increased with increasing CNT content, while the intensities of the Al 2 Cu peaks varied less significantly. This was in good agreement with the XRD results shown in Fig.6 about the appearance of small Al 4 C 3 peaks in the composite and the persistence of Al 2 Cu compared with the base alloy.…”
Section: The Presence Of Aluminum Carbide Al 4 C 3 Suggests the Occurmentioning
confidence: 99%
See 3 more Smart Citations